The Correlation Between British Virtual Materials and Improving EFL ‎Students' ‎Vocabulary and British Chunks Awareness - Abdullah A. Hardan (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This study aims to investigate the correlation between learning English language via British virtual materials and the improvement of the students' vocabulary and British chunks awareness. Methodology: Eighteen (18) male and female students chosen from taken from 2nd grade at the Department of English, College of Education for Humanities to take place in the study. A semi-structured- interview and ClassVR and Mondly VR tools were used for collecting data. A rubric model was prepared to categorize the participants' answers. Results: The results revealed that there was high correlation between the use of British virtual materials and students' vocabulary improvement, the students learned vocabulary from authentic British context that they did not expose to in the syllabus and can last for life such as how to say "I am tired" (the levels of tiredness): I'm tired to the bone; I'm exhausted; I'm dog-Tired; I'm dragging; and I'm running on empty. These expressions will be different if the learner translates from Arabic to English and vice versa. In addition, the results revealed that British virtual materials have improved students' awareness of the British chunk and understanding the culture such as engaging with the virtual guide of the British Museum and gain good information